Matrix metalloproteinases: their functional role in lung cancer. (16th June 2017) - Merchant, Neha; Nagaraju, Ganji Purnachandra; Rajitha, Balney; Lammata, Saipriya; Jella, Kishore Kumar; Buchwald, Zachary S; Lakka, Sajani S; Ali, Arif N
Summary: MMPs play an important role in tumor progression and metastasis, including ECM degradation, modification of the cell–cell and cell–ECM interactions, invasion, migration and angiogenesis. This review critically assesses the role of MMPs in relation to cancer growth and future prospects. Abstract: Lung malignancy is the foremost cause of cancer-related deaths globally and is frequently related to long-term tobacco smoking. Recent studies reveal that the expression of matrix metalloproteinases (MMPs) is extremely high in lung tumors compared with non-malignant lung tissue. MMPs are zinc-dependent proteases and are involved in the degradation of extracellular matrix (ECM). Several investigations have shown that MMPs manipulate the activity of non-ECM molecules, including cytokines, growth factors and receptors that control the tumor microenvironment. In this review, we have summarized and critically reviewed the published works on the role of MMPs in non-small-cell lung cancer. We have also explored the structure of MMPs, their various types and roles in lung cancer metastasis including invasion, migration and angiogenesis.